Tumor Cell-Specific and Lipase-Responsive Delivery of Hydrogen Sulfide for Sensitizing Chemotherapy of Pancreatic Cancer - Tian, Libing; Pei, Rui; Zhang, Xiaojun; Li, Kun; Zhong, Yuting; Luo, Yougen; Zhou, Shu-Feng; Chen, Lichan (Frontiers in Bioengineering and Biotechnology, 2022)
The inability of small molecule drugs to diffuse into tumor interstitium is responsible for the relatively low effectiveness of chemotherapy. Herein, a hydrogen sulfide (H2S) gas involved chemosensitization strategy is proposed for pancreatic cancer treatment by developing a tumor-specific lipase-responsive nanomedicine based on aptamer-conjugated DATS/Dox co-loaded PCL-b-PEO micelle (DA/D@Ms-A). After receptor-mediated endocytosis and subsequent digestion of PCL blocks by intracellular lipase, the nanomedicine releases Dox and DATS, which then reacts with intracellular glutathione to produce H2S. The cytotoxicity result indicates that H2S can enhance Dox chemotherapy efficiency owing to the synergetic therapeutic effect of Dox and H2S. Moreover, the nanomedicine is featured with well tumor penetration capability benefitting from the targeting ability of aptamers and high in vivo biocompatibility due to the high density of PEO and biodegradable PCL. The nanomedicine capable of synergetic gas-chemo therapy holds great potential for pancreatic cancer treatment.